The Evolution of the Scavenger Receptor Cysteine-Rich Domain of the Class A Scavenger Receptors - Yap, Nicholas V. L.; Whelan, Fiona J.; Bowdish, Dawn M. E.; Golding, G. Brian (Frontiers in Immunology, 2015)
The class A Scavenger Receptor (cA-SR) family is a group of five evolutionarily related innate immune receptors. The cA-SRs are known for their promiscuous ligand binding; as they have been shown to bind bacteria such as Streptococcus pneumoniae, and Escherichia coli, as well as different modified forms of low-density lipoprotein. Three of the five family members possess a Scavenger Receptor Cysteine Rich (SRCR) domain while the remaining two receptors lack the domain. Previous work has suggested that the Macrophage Associated Receptor with COllagenous structure (MARCO) shares a recent common ancestor with the non-SRCR-containing receptors; however the origin of the SRCR domain within the cA-SRs remains unknown. We hypothesize that the SRCR domains of the cA-SRs have a common origin that predates teleost fish. Using the newly available sequence data from sea lamprey and ghost shark genome projects, we have shown that MARCO shares a common ancestor with the SRCR-containing proteins. In addition, we explored the evolutionary relationships within the SRCR domain by reconstructing the ancestral SRCR domains of the cA-SRs. We identified a motif that is highly conserved between the cA-SR SRCR domains and the ancestral SRCR domain that consist of WGTVCDD. We also show that the GRAEVYY motif, a functionally important motif within MARCO, is poorly conserved in the other cA-SRs and in the reconstructed ancestral domain. Further, we identified three sites within MARCO’s SRCR domain which are under positive selection. Two of these sites lie adjacent to the conserved WGTVCDD motif, and may indicate a potential biological function for these sites. Together these findings indicate a common origin of the SRCR domain within the cA-SRs; however different selective pressures between the proteins may have caused MARCOs SRCR domain to evolve to contain different functional motifs when compared to the other SRCR-containing cA-SRs.